The Understanding and Emotion Caused by an Architect-Built Space Using Music - Tavakoli, Davod Baradaran; Bareshadat, Negin; Tafrishi, Maryam (Journal of History Culture and Art Research, 2017)
Music and architecture are two of the effective components of the lives of human beings which are especially important. However, the link between these two components and their impacts on the understanding of the audience are some of the issues which have not been focused on. This bond is caused by a mutual space. A space which can either be created by a work of architecture or a piece of music. Despite of the previous studies that focused on investigating the different aspects of these two forms of art that link them together, this paper aims to discover and understand the perceptual – emotional relationship between music and architecture further than the preliminary principles that link them. It also aims to find an answer to this question: how can a relationship be established between various linking aspects of these two arts that would be understandable for their audiences? The present study is an analytical – descriptive research that relies on library studies and uses a logical argument in order to analyze, interpret and compare the relationship between music and architecture and its impact on the understanding of the audience. Accordingly, after reviewing the research literature and stating the concept of space in architecture and music, the linking aspects of these two forms of art have been comparatively analyzed. According to the conclusion of results, by taking into consideration various frequencies and generation of a variety of geometrical orders in each frequency, the more intense music is the more complex its spatial impact will be on the feeling and understanding of the audience.